JUMLAH DAN BENTUK KONSUMSI UBI SEBAGAI PENGGANTI MIE INSTAN DITINJAU DARI GOLONGAN PENDAPATAN DI KOTA PALEMBANG - WP, Yudhi Zuriah; Alfiati, Siska (AGRIPITA JOURNAL, 2017)
This study aims to quantify the amount and form of consumption of the population on instant noodles and cassavas in the city of Palembang. The sampling method used in this study is disproportioned statified random sampling on 90 households of observed farmers located on three research sites in Palembang. The analysis results indicate that each household in a month consumes instant noodles on high-income/upper-middle, middleincome and low-income are 2.99 kilograms, 3.33 kilogram, and 4.70 kilograms respectively. Two types of instant noodles are fried-noodles and gravy-noodles. Meanwhile for the cassavas consumptions for each household monthly are 5.35 kilograms, 1.76 kilograms and 20.20 kilograms for high-income/upper-middle, middle-income and lowincome respectively on two types of cassavas which are sweet potatoes and cassavas. Other types of cassavas are fresh-cassavas and processed-cassavas.